Shifting Boundaries Between the Religious and the Secular: Religious Organizations in Global Public Space - Lehmann, Karsten (Journal of religion in Europe, 2013)
The aim of the article is to add a religious studies perspective to the recent debates on the establishment of religion in public space. In light of this background, it highlights the global dimension of the corresponding processes by analyzing the early developments of religious non-governmental organizations formally accredited to the United Nations organization (UN). Based upon three case analyses—the Commission of the Churches on International Affairs, Pax Romana, and the Friends World Committee for Consultation—the article presents a two-fold argument. On the one hand, it makes the point that these organizations started out to approach the UN context in quite distinct ways drawing upon core ideas of their respective tradition in order to frame their activities. On the other hand, they adapted to the structures of the UN in order to act efficiently. This triggered shifts in the internal boundaries between the religious and the secular.